Evaluasi Pemungutan Pajak Bumi Dan Bangunan (PBB) Di Desa Pusungi Kec. Ampana Tete, Kab. Tojo Una-una - N. Novrianti; Tety Thalib; Misbahudin Djaba (Public Inspiration : Jurnal Administrasi Publik, 2025)
This study aims to evaluate the implementation of Land and Building Tax (PBB) collection in Pusungi Village, Ampana Tete Sub-district, Tojo Una-Una Regency. The evaluation focuses on using the CIPP model (Context, Input, Process), developed by Stufflebeam. The research employs a descriptive method with a qualitative approach. Data were collected through observation, interviews, and documentation. The findings indicate that in the context aspect, there are still discrepancies between tax object data and the Tax Due Notification Letter (SPPT), as well as delays in reporting and land ownership by individuals who are not yet Indonesian citizens (WNI). In the input aspect, the billing process still relies on manual forms and lacks support from a digital system, along with limited operational facilities for village tax officers. Meanwhile, in the process aspect, there are challenges in socialization, data collection, and taxpayer compliance, particularly regarding inherited land or land that has changed hands without administrative updates. Although the payment realization rate reached 72.6%, there is still untapped revenue potential. Overall, the implementation of PBB collection in Pusungi Village is deemed suboptimal. This evaluation suggests the need for improvements in the data collection system, enhancement of billing facilities, and stronger synergy between the village government and related institutions. With accurate data updates and the use of an integrated information system, it is hoped that future PBB collection can be conducted efficiently, transparently, and support sustainable village development.